FIXED POINT THEOREMS FOR (ψ, ϕ, ω)-WEAK CONTRACTIONS IN COMPLETE METRIC SPACES - Pasangka, Irvandi Gorby; Kleden, Maria Agustina; Putra, Ganesha Lapenangga; Purnami, Ndaru Atmi (Journal of the Indonesian Mathematical Society, 2024)
In this paper, we define the mapping called (ψ, ϕ, ω)-weak contractions. We then use this definition to proof the existence of fixed point. The mapping we defined above is a modified mapping by Liu and Chai. We use the concept ω-distance to proof the fixed point theorem. Since every ω-distance is metric, then the resulting theorem also satisfy for every metric.